The Status of Bottom Hand Line Catch in Buyat Bay - Fransisco P.T Pangalila, 1; Jhonny Budiman, 2; Aglius T.R. Telleng, 3; Emil Reppie, 4 (Journal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
The purpose of this study was to determine the status of demersal fishing and make a thematic map location of the fishing activities. The research was carried out around Buyat Ratatotok Southeast Minahasa regency, for 7 months beginning with the planning phase tothe writing of the report. This research was done by using a survey method that is based on adescriptive approach. Caught as many as 96 species of fish catches dominant base with as many as 12 types, namely trevallies buliling and blue (Carangoides gymnostethus), trevallies pongko (Carangoides fulvoguttatus), trevallies box, yellow and Wayan (Carangoides ferdau), trevallies Napo and trevallies lao (Citula armatus), trevallies mopi (Caranx ignobilis), trevallies sangkalade and sangkapete (Carangoides uii) and trevallies Sepo (Seriola dumerili). All types of fish caught by rod dodango . Basic fishing season occurs during the seven months of the year, in January and March, then in May to July and in November and December. Maximum sustainable catches made as many as 25 trips per day by the number of catches as many as152 birds. The average size of the catch weight of 1.5 kg or so carrying capacity of 228 kg of biomass per day. When per kg catch for Rp.10.000,- then every fisherman has a revenue of Rp. 90.000,- per day basis tertagkap fish in the waters around Buyat with the locations of existing Napo with a depth range between 30 and 80 meters.